A Friction of Cultural Values and Characteristics of Imperial Mosque in Ternate - tayeb, muhammad; Asriany, Sherly; Ridwan, Ridwan (Journal of Islamic Architecture, 2015)
Indonesia has many religious culture that should be preserved one ofÂ  which is the imperial mosque. Most of the imperial mosque has its own characteristics in carrying out activities both religious and cultural. Sultanate of Ternate is the largest sultanates in eastern Indonesia which would give other peculiarities that need to be raised as a typical Indonesian culture. The purpose of this study is to identify the type of tradition in doing at the mosque sultanate by people of Ternate and changes in cultural values of the people of Ternate in the imperial mosque. In this study found the phenomenon characteristic changes in cultural values by linking changes in the physical aspect and non-physical. To determine the effect of these factors, the method used is the method of observation of physical traces. This method is expected to be able to explain the effect of the change occurred. Based on the results of the study indicate compliance is still customary rules of religious traditions in the imperial mosque although some traditions that formerly taboo has been done, the progress of the times, increase knowledge, and make the implementation of the reform and renewal of cultural values carried by the community for various reasons theTernate.